HPLC–MS/MS method to measure trabectedin in tumors: preliminary PK study in a mesothelioma xenograft model. (August 2015) - Ceriani, Laura; Ferrari, Mariella; Zangarini, Monique; Licandro, Simonetta Andrea; Bello, Ezia; Frapolli, Roberta; Falcetta, Francesca; D'Incalci, Maurizio; Libener, Roberta; Grosso, Federica; Aviles, Pablo; Zucchetti, Massimo
Background: Trabectedin is an anticancer agent registered for the second-line treatment of soft tissue sarcoma and ovarian cancer. No preclinical data are available on its tumor distribution, so a method for quantification in neoplastic tissues is required.Methods/results: We validated an LC–MS/MS assay determining the recovery, sensitivity, linearity, precision and accuracy in mouse tumor and liver samples. The limit of quantification was 0.10 ng/ml with a curve range of 0.10–3.00 ng/ml (accuracy 96.1–102.1%). Inter-day precision and accuracy of QCs were 6.0–8.2 and 97.0–102.6% respectively. The method was applied in mesothelioma xenografts treated with therapeutic doses.Conclusion: The method was validated for measuring trabectedin in tissues. In a mesothelioma xenograft model, trabectedin distributed preferentially in tumor compared with liver.